Neuroinflammation drives anxiety and depression in relapsing-remitting multiple sclerosis. (26th September 2017) - Rossi, Silvia; Studer, Valeria; Motta, Caterina; Polidoro, Serena; Perugini, Jacopo; Macchiarulo, Giulia; Giovannetti, Ambra Mara; Pareja-Gutierrez, Lorena; Calò, Andrea; Colonna, Isabella; Furlan, Roberto; Martino, Gianvito; et al.
Abstract : Objective: To explore the inflammatory processes in the pathogenesis of psychiatric symptoms and the prognostic value of psychiatric comorbidities in multiple sclerosis (MS). Methods: Four hundred five patients with relapsing-remitting (RR) MS underwent psychiatric evaluation by means of Beck Depression Inventory II (BDI-II) and State/Trait Anxiety Inventory (STAI-Y). The inflammatory activity level was assessed by MRI. In a subset of 111 treatment-naive patients, CSF levels of proinflammatory cytokines were determined. Correlation and regression analyses were performed to determine associations between variables. Results: Relapsing patients demonstrated greater values of STAI-state and BDI-II compared with remitting patients but comparable trait-anxiety scores. There were no significant differences in psychometric parameters between relapsing and asymptomatic MRI-active patients, highlighting the effect of subclinical inflammation on mood disturbances. A significant reduction of STAI-state and BDI-II scores was recorded, along with the subsiding of neuroinflammation. Interleukin-2 CSF levels were found to correlate with STAI-state, while tumor necrosis factor-α and interleukin-1β correlated with BDI-II. Because emotional disorders were associated with subclinical inflammation, variations of the psychometric profile were able to detect subclinical reactivation earlier. In line with this, high STAI-state values considerably predicted the possibility of disease reactivation. Conclusions: Mood alterations are induced by intrathecal inflammation, even though not clinically apparent, and are able to predict inflammatory reactivations in RRMS. Inflammation is therefore a biological event, not less important than the traditional psychosocial factors, involved in mood disorders.